2018
DOI: 10.1101/373811
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling membrane nanotube morphology: the role of heterogeneity in composition and material properties

Abstract: Membrane nanotubes have been identified as a dynamic way for cells to connect and interact over long distances. These long and thin membranous protrusions have been shown to serve as conduits for the transport of proteins, organelles, viral particles, and mRNA. Nanotubes typically appear as thin and cylindrical tubes, but they can also have a beads-on-a-string architecture. Here, we study the role of membrane mechanics in governing the architecture of these tubes and show that the formation of a bead-like stru… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Therefore, in most cases, analytical solutions are not possible and the equations are often solved numerically. Over the last few decades, various computational approaches have been developed to solve the set of governing PDEs including the boundary value problem for axisymmetric coordinates [32,66,73,120,121], different finite element methods [122,123,124], Monte Carlo methods [125,126,127], finite difference methods [128,129], and the phase field representation of the surface [130,131,132]. Each of these methods has its own advantages and disadvantages and, depending on the complexity of the problem, one or more of them can be implemented.…”
Section: Theoretical Models Of Biological Membranesmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, in most cases, analytical solutions are not possible and the equations are often solved numerically. Over the last few decades, various computational approaches have been developed to solve the set of governing PDEs including the boundary value problem for axisymmetric coordinates [32,66,73,120,121], different finite element methods [122,123,124], Monte Carlo methods [125,126,127], finite difference methods [128,129], and the phase field representation of the surface [130,131,132]. Each of these methods has its own advantages and disadvantages and, depending on the complexity of the problem, one or more of them can be implemented.…”
Section: Theoretical Models Of Biological Membranesmentioning
confidence: 99%
“…By using the SC model, recent studies have shown for example how a line tension at a lipid phase boundary could drive scission in yeast endocytosis [32,144,145], or how a snap-through transition from open U-shaped buds to closed buds in CME is regulated by the membrane tension [66,73]. Furthermore, the experimentally observed change in the membrane tension (spontaneous tension) in response to protein adsorption [146,147,148], can be explained in the context of the SC model [120,136,140]. The SC model has also been used to elucidate the role of varying membrane tension due to protein-induced spontaneous curvature [120,136,140].…”
Section: Continuum Elastic Energy Models Of Membrane–protein Intermentioning
confidence: 99%
See 2 more Smart Citations
“…• We assume that the membrane is locally inextensible, since the stretching modulus of the lipid bilayer is an order of magnitude larger than the membrane bending modulus [91]. We implemented this constraint using a Lagrange multiplier, which can be interpreted as the membrane tension [92][93][94]. We note that this membrane tension, in this study, is better interpreted as the cortical tension including the effective contribution of both the membrane in-plane stresses and membrane-cytoskeleton interactions [95,96].…”
mentioning
confidence: 99%